Интегралы содержащие a+bx

\[ \int \frac[-1.1]{dx}{a+bx} = \frac{1}{b}\ln(a+bx)+C \]
\[ \int (a+bx)^n dx = \frac{(a+bx)^{n+1}}{b(n+1)}+C \]
\[ \int \frac[-1.1]{x dx}{a+bx} = \frac[-1.5]{1}{b^2}[a+bx-a·\ln(a+bx)]+C \]
\[ \int \frac[-1.1]{x^2 dx}{a+bx} = \frac[-1.5]{1}{b^2}[\frac{1}{2}(a+bx)^2-2a·(a+bx)+a^2·\ln(a+bx)]+C \]
\[ \int \frac[-1.1]{dx}{x(a+bx)} = -\frac[-1.1]{1}{a}\ln(\frac{a+bx}{x})+C \]
\[ \int \frac[-1.5]{dx}{x^2(a+bx)} = -\frac[-1.1]{1}{ax}+\frac[-1.5]{b}{a^2}\ln(\frac{a+bx}{x})+C \]
\[ \int \frac[-1.5]{x dx}{(a+bx)^2} = \frac[-1.5]{1}{b^2}[\ln(a+bx)+\frac{a}{a+bx}]+C \]
\[ \int \frac[-1.5]{x^2 dx}{(a+bx)^2} = \frac[-1.5]{1}{b^3}[a+bx-2a·\ln(a+bx)-\frac{a^2}{a+bx}]+C \]
\[ \int \frac[-1.5]{dx}{x(a+bx)^2} = \frac[-1.1]{1}{a(a+bx)}-\frac[-1.5]{1}{a^2}\ln(\frac{a+bx}{x})+C \]
\[ \int \frac[-1.5]{x dx}{(a+bx)^3} = \frac[-1.5]{1}{b^2}[-\frac{1}{a+bx}+\frac[-1.5]{a}{2(a+bx)^2}]+C \]

Интегралы содержащие a+bx

стр. 852